Complexity of athletic fitness with regard to selection and talent prognosis by a physiological viewpoint - Ulmer, H. V. (International Scientific Conference Social and Biomedical Aspects of Teenage Soccer in the Context of European Integration, Krakow, 29. April to 1. May 2004, 2004)
Athletic fitness depends on a complex interaction of different performance-related factors. It is typical for these factors, that they are specific for an athletic discipline, each of it, and that they can be differentiated into factors which are measurable and which are not measurable by tests. Sport scientists like it to test their athletes. It is necessary to admonish them: Be careful in handling the results with regard to the complexity of athletic fitness, even less if prognoses (talent searching) are made. In soccer rating is better than testing and testing better than using a dice. False negative and false positive decisions cannot be avoided; the percentage of false negative decisions should be very small, however. With regard to the test criteria sensitivity and specifity this is only possible by accepting a high percentage of false positive decisions in talent searching Adjudicating, scoring or testing, in all cases experience is necessary. Diagnoses of athletic fitness and prognoses are to manage by integration of objective and subjective parameters. Therefore the coach`s view is very important and the most experienced coaches should be engaged in talent searching in teenagers.